Romantic comedy : a novel [large type] - Sittenfeld, Curtis (Random House Large Print, 2023)
A sketch writer for a late-night comedy show, Sally Milz pokes fun at the phenomenon of talented but average men who've gotten romantically involved with beautiful women and how the reverse never happens, until she meets a pop music sensation who flips the script on all her assumptions.